PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN PADA RESTORAN AYAM BAKAR WONG SOLO - Vandrias Dewantoro; Darmadi Darmadi; Rani Fitri Utami (Jurnal Dinamika Sosial Ekonomi, 2010)
The Influence of Service Qualify to Satisfaction and Customer Loyality of Ayam Bakar Wong Solo Restaurant in Yogyakarta. This research aim to analyze the influence of service quality to satisfaction and customer loyalty of Ayam bakar Wong solo restaurant. Sampling method used is convenience sampling with 100 sampels. Testing of hypothesis uses structural equation modeling analysis. The conclusion of this research is service quality are positively influence the satisfaction and customer loyaltyKeywords: service quality, customer satisfaction, customer Ioyality.